Domiciliary Alzheimer visiting in Down syndrome pilot project: Preliminary results: Implementation of person‐centered care. (7th December 2020) - Valldeneu, Sílvia; Barroeta, Isabel; Altuna, Miren; Videla, Laura; Benejam, Bessy; Estellés, Teresa; Fernandez, Susana; Lleó, Alberto; Blesa, Rafael; Fortea, Juan; Carmona‐Iragui, Maria
Abstract: Introduction: People with Down syndrome (DS) are at ultra‐high risk of developing Alzheimer's disease (AD). A comprehensive health care approach is needed to enable an early diagnosis and an individualized follow up. The Alzheimer‐Down Unit developed a health plan which is offered to every adult with Down syndrome in Catalonia and which includes annual neurological and neuropsychological assessments together with clinical support and social counseling when needed. Within this plan, the "Domiciliary Alzheimer Visiting in Down syndrome" (DAVIS) pilot project adds domiciliary visits to bring closer this plan to those candidates who are not able to come to our site. In the present study, we analyze the preliminary results of this project. Methods: Pilot observational cross‐sectional study. We contacted occupational centers /residences which included users with Down syndrome and we organized the visit of a neurologist and a neuropsychologist from our team. Candidates and their caregivers were informed about the health plan and those who accepted to participate were assessed. According to their cognitive status, they were classified into 3 groups: without cognitive impairment (aDS), prodromal AD (pDS) or AD dementia (dDS). Subsequently, a physically present or telephonic follow‐up visit, together with the option of collaborating with Primary Care, was offered. Participation in biomarkers research projects was also proposed. Results: Between October 2018 and December 2019 we assessed 92 participants (mean age 42.5, 48.9% males) classified as aDS (77.1%), pDS (4.4%) or dDS (18.5%). The 67.4% and the 28.3% of the participants were recruited to continue with the physically present or telephonic follow‐up, respectively. A 10.9% of the participants agreed to collaborate on research projects. Conclusions: The DAVIS pilot project facilitates the dissemination of our comprehensive health plan for adults with DS in Catalonia. Its clinical application allows the diagnosis of new cases of AD and brings closer research to the adult population with DS. The DAVIS pilot project emphasizes the need of social and health care improvements for adults with DS; however, an extended DAVIS project will generate solid data to influence on health policy and, potentially, to improve the people with DS and their caregivers quality of life.